Enhancing Legal Literacy to Prevent Early Marriage and Domestic Violence: A Community Service Program at Madrasah Aliyah Miftahul Hasanah Gondosuli - Marzuki, Ismail; Aini, Kudrotun; Atia, Milda; Nirmala Fitriannida, Lyra; Istikamatul Amelia (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Child marriage and domestic violence (KDRT) remain prevalent social issues in rural areas, including around Madrasah Aliyah Miftahul Hasanah, Gondosuli Village, often driven by low legal awareness and strong cultural pressure. Based on this condition, this community service program aimed to enhance legal literacy among Islamic high school students, enabling them to understand, identify, and prevent child marriage and domestic violence through a preventive educational approach. This program was conducted by observing the conditions of partners, interviewing various parties, and interacting directly with madrasah aliyah students. The results of this program showed a significant increase in students' understanding of the legal age for marriage and the forms of domestic violence. The indicators of the results of this activity are demonstrated through an increase in students' understanding of the minimum age for marriage, their ability to identify forms of violence, and the emergence of reflective awareness among students to communicate issues openly. In conclusion, preventive legal education proved effective in improving students’ legal awareness. This program recommends integrating basic legal topics into non-formal educational activities within the madrasah and strengthening collaboration between educational institutions and universities in protecting children and preventing community-based violence